Corporate governance and leadership from an Islamic perspective - Khaliq, Ahmad (2018)
The focus on the study of management so far has been mainly on two elements- work (production) and workers’ welfare. Hence the management as well as leadership grid has evolved over years based on these two. Experts did not spare a thought that human is also a spiritual being. Western institutions very recently realized a missing element of spirituality from literature on management. Several years ago, the idea that any religion—let alone Islam—could help us manage things better would have been unthinkable. However, with all the corporate scandals that have plagued the world over the past 20 years, people are realizing that it might be a good thing if corporate leaders had a greater sense of morality, that is an of shoot of spirituality. Thus in today’s governance, a good corporate leadership seems to be in short supply due to the lack of spirited executives. This is specifically true in the Muslim world but it is increasingly true in developed countries as well. Studies indicate that what worked yesterday will be met by rising popular discontent and it may not work today. Thus leadership faces two ways of tackling today’s corporate governance problem. First, one can do more of the same. Second, one can try something different. The Islamic perspective to governance and leadership is interesting, not because it is new, but because it worked in the past. For over 1,400 years, Muslim leaders have demonstrated sound leadership qualities and developed a great civilization based on fair governance.